2009
DOI: 10.1016/j.jmacro.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Openness, income-tax progressivity, and inflation

Abstract: This paper considers a model of an open economy in which the degree of income-tax progressivity influences the interaction among openness, central bank independence, and the inflation rate. Our model suggests that an increase in the progressivity of the tax system induces a smaller response in real output to a change in the price level. This implies that increased incometax progressivity reduces the equilibrium inflation rate and that the effect of increased income-tax progressivity on inflation is smaller whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Badinger (2009) has obtained results consistent with this prediction in an analysis of data from 91 countries over the [1985][1986][1987][1988][1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004] interval. Recent work has added other elements that can impinge on the relationship between trade openness and the sacrifice ratio: political regime (Caporale and Caporale, 2008), progressivity of income taxation (Daniels and VanHoose, 2009a), capital mobility (Daniels and VanHoose, 2009b), labor-market structures (Bowdler and Nunziata, 2010), reliance on imported commodities in production (Pickering and Valle, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Badinger (2009) has obtained results consistent with this prediction in an analysis of data from 91 countries over the [1985][1986][1987][1988][1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004] interval. Recent work has added other elements that can impinge on the relationship between trade openness and the sacrifice ratio: political regime (Caporale and Caporale, 2008), progressivity of income taxation (Daniels and VanHoose, 2009a), capital mobility (Daniels and VanHoose, 2009b), labor-market structures (Bowdler and Nunziata, 2010), reliance on imported commodities in production (Pickering and Valle, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2SLS results indicated that larger trade and financial openness reduced central bank's independency which yield to less inflation that is attached with larger output-inflation tradeoff. Daniels and Vanhoose (2007) considered open economy with degree of incometax progressivity influenced on the interaction between openness, central bank independence and prices by using data of 17 countries from 1979 to 1999. Regression analysis of cross-country inflation provided favor inverse relationship between inflation 11 Hong Kong, Korea, Mexico, Philippines, Singapore, and Taiwan. 12 Canada, France, Germany, Italy, Japan, U.K. and the United States.…”
mentioning
confidence: 99%
“…show that an increased responsiveness of domestic spending to the real terms of trade and an enlargement of the share of domestic labor markets with nominal rigidities also cause output to be more responsive to inflation, and Daniels and VanHoose (2009a) show that increased progressivity of income taxation can have a similar effect. In addition, Daniels, Nourzad, and VanHoose (2005) suggest that any factor, such as a greater degree of openness or an increase in central bank independence, that has the effect of pushing down mean inflation can also lead to greater nominal rigidities.…”
Section: How Greater Openness Might Make Aggregate Output More Inflatmentioning
confidence: 91%